The effect of nurses’ ethical leadership and ethical climate perceptions on job satisfaction - Özden, Dilek (Nursing ethics, 2019)
Background:The development of ethical leadership approaches plays an important role in achieving better patient care. Although studies that analyze the impact of ethical leadership on ethical climate and job satisfaction have gained importance in recent years, there is no study on ethical leadership and its relation to ethical climate and job satisfaction in our country.Objectives:This descriptive and cross-sectional study aimed to determine the effect of nurses’ ethical leadership and ethical climate perceptions on their job satisfaction.Methods:The study sample is composed of 285 nurses who agreed to participate in this research and who work at the internal, surgical, and intensive care units of a university hospital and a training and research hospital in İzmir, Turkey. Data were collected using Ethical Leadership Scale, Hospital Ethical Climate Scale, and Minnesota Satisfaction Scale. While the independent sample t-test, analysis of variance, Mann–Whitney U test, and Kruskal–Wallis test were used to analyze the data, the correlation analysis was used to determine the relationship between the scales.Ethical considerations:The study proposal was approved by the ethics committee of the Faculty of Medicine, Dokuz Eylül University.Findings:The nurses’ mean scores were 59.05 ± 14.78 for the ethical leadership, 92.62 ± 17 for the ethical climate, and 62.15 ± 13.46 for the job satisfaction. The correlation between the nurses’ ethical leadership and ethical climate mean scores was moderately positive and statistically significant (r = +0.625, p = 0.000), was weak but statistically significant between their ethical leadership and job satisfaction mean scores (r = +0.461, p = 0.000), and was moderately positive and statistically significant between their ethical climate and job satisfaction mean scores (r = +0.603, p = 0.000).Conclusion:The nurses’ ethical leadership, ethical climate, and job satisfaction levels are moderate, and there is a positive relationship between them. The nurses’ perceptions of ethical leadership are influenced by their educational status, workplace, and length of service.